Determining the effect of transformable air ducts and a heat-reflecting screen inside them on the thermal-humidity condition of the corner element considering significant seasonal temperature gradients - Zhangabay, Nurlan; Ibraimova, Ulzhan; Tursunkululy, Timur; Duissenbekov, Bolat; Urmashev, Bagdaulet; Utelbayeva, Akmaral; Shayakmet, Shugyla (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates a corner element in a multi-story building with varying numbers of stories. The task addressed relates to the vulnerability of building corner elements to temperature fluctuations. The energy efficiency of corner elements in external wall structures of buildings with vertical air ducts and a heat-reflecting screen was numerically evaluated under conditions of significant seasonal temperature gradients and varying numbers of stories. The thermal and humidity conditions of corner zones in building envelopes, characterized by spatial heat transfer and increased thermal vulnerability, were analyzed. Numerical modeling was performed using the finite element method in the ANSYS programming environment, using coupled heat and moisture transfer calculations under various climatic scenarios. The influence of corner zone geometry and building height on temperature distribution and the risk of condensation in the outer envelope was analyzed. The study results showed that in winter, pronounced non-uniformity of the temperature field occurs in corner zones due to the thermal bridge effect. Moreover, the relative temperature reduction in the corner zone, compared to straight wall sections, ranges from 7% to 12%. During transitional and summer periods, temperature gradients are significantly reduced, and the influence of building height is insignificant. Analysis of the humidity regime revealed the possibility of short-term condensation without conditions for long-term moisture accumulation. The results could be used in the design of energy-efficient adaptive external wall structures for buildings in regions with pronounced seasonal temperature fluctuations